Hyphenation of field‐amplified sample injection and transient isotachophoresis in CE for the determination of sotalol and metoprolol in human urine samples. Issue 11 (10th March 2020) - Xu, Lei; Meng, Weiqi; Lu, Jing; Cui, Fengjuan; Gao, Lidi; Chen, Lin; Xin, Yang
Abstract: A sensitive approach of capillary electrophoresis coupled with field‐amplified sample injection and transient isotachophoresis was developed for the simultaneous determination of two β‐blockers: sotalol and metoprolol. In this dual focusing technique, the samples were prepared via only dissolution in ultrapure water and then injected electrokinetically. Phosphate acted as both the background electrolyte and the leading electrolyte. Its optimized concentration was 80 mM. A total of 25 mM of glycine was used as the terminating electrolyte. Under optimum conditions, good separation of sotalol and metoprolol was achieved within 10 min. In comparison with the conventional method, the sensitivity enhancement factors were up to 1031 and 919 for sotalol and metoprolol, respectively. The proposed method was employed in the determination of sotalol and metoprolol in spiked human urine samples. The limits of detection and limits of quantitation obtained via ultraviolet detection were 5 and 12 ng/mL, respectively, for sotalol, and 10 and 25 ng/mL, respectively, for metoprolol. The intraday repeatability values were lower than 2.7 and 1.7% for peak area and migration time, respectively. The assay is a simple and efficient strategy with potential for application in clinical and biochemical laboratories for monitoring sotalol and metoprolol.